Students’ Creative Industry Development: A Community Based Research in STIE Sumbar - Reflianto Reflianto; Nurtati Nurtati; Novi Yanti (Intervensi Komunitas, 2020)
The rate of educated unemployment in Indonesia requires educational institutions, especially universities or college to strengthen the entrepreneurship curriculum that could deliver some new entrepreneurs, which in turn can reduce the educated unemployed. Purpose of this paper is to share experiences in the community service activities in the development of creative industries of digital printing for college students. The development of creative industries involved student community of STIE Sumbar. This program provides training creative industry of digital printing to produce a variety of merchandise products. The target of this program was delivering new entrepreneurs among students for a more active role in the creative economy industry. In addition, this program is also to strengthen the entrepreneurial spirit of students in Higher Education. Projects carried out during these six months and has already provided the knowledge and entrepreneurship training, and has opened up opportunities and strategies for students to build a creative economy industry in a wide range of digital printing products that have high demand levels for the academic activities of national conference and internasiona for example banner, logo and t-shirts. Basis expertise provided in this training is the ability to create a design by using Corel Draw program to create a range of innovative merchandise. The project has been successfully delivered ten new entrepreneurs in the field of creative industry of digital printing. For local government is expected to support this program by issuing a regulation on the development of creative industry housing for college students. meanwhile for higher education institution is expected to collaborate together in building a creative economy business program at the college level through joint college community.